Pengembangan Media Belajar Model-Model Boneka Dari Bahan Kain Flanel Berdasarkan Tema Kegiatan Untuk Pembelajaran Anak Usia Dini - Usep Kustiawan; Wuri Astuti; Munaisra Tri Tirtaningsih (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2020)
The use of appropriate learning media in kindergarten can develop a variety of children's abilities well, but conversely, if the use of media is less attractive to children, children will quickly get bored and are no longer interested in learning provided by the teacher. The purpose of this research is to develop learning media for doll models that can be used to develop children's expressive language skills in storytelling in accordance with the types of theme activities that exist in kindergarten. This research is a research development that adopts the development stages of Borg and Gall. The results showed that the developed media products were easy for students to use and had a high level of attractiveness.